PENGARUH PENATAAN RUANG LUAR TERHADAP KENYAMANAN DI PEDESTRIAN KAWASAN JALAN KYAI TAPA GROGOL JAKARTA BARAT - Priyambodo, Dimas Agung; Khuluk, Nazaruddin (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2022)
Pedestrian paths are one of the completeness of a city, whose existence is needed by the citizens of the city concerned to be able to move easily, safely and comfortably from one place to another. outdoor spatial planning function in protecting the environment and sustainability in the Kyai Tapa street area. The pedestrian location is in the Kyai Tapa Grogol Street area, West Jakarta. This research uses qualitative research with a descriptive approach which produces descriptive data in the form of written and spoken words from informants research and the observed behavior of the research object. The result is that most of the comfort standards for the pedestrian pathways in the Kyai Tapa street area have fulfilled the wishes of pedestrians, it's just that on the cleanliness criteria there is still an uneven placement of trash cans. So more development is needed both on the variable pedestrian path comfort which still does not meet the wishes of pedestrians.